4-Chlorophenol degradation using ultrasound/peroxymonosulfate/nanoscale zero valent iron: Reusability, identification of degradation intermediates and potential application for real wastewater. (June 2018) - Barzegar, Gelavizh; Jorfi, Sahand; Zarezade, Vahid; Khatebasreh, Masoumeh; Mehdipour, Fayyaz; Ghanbari, Farshid
Abstract: In this study, nanoscale-zero valent iron (nZVI) was synthesized and its function was assessed in ultrasound (US)/peroxymonosulfate (PMS)/nZVI process to degrade 4-chlorphenol (4-CP). The influential operation parameters of US/PMS/nZVI were evaluated on 4-CP degradation. 95% of 4-CP was degraded during 30 min under the conditions of pH = 3.0, nZVI = 0.4 g/L, PMS = 1.25 mM, US power = 200 W. The rate constants of 4-CP degradation for US/PMS/nZVI, PMS/nZVI, US/PMS and US/nZVI were 0.1159, 0.03, 0.0134 and 0.0088 min −1 respectively. Simultaneous application of US and nZVI synergistically increased 4-CP degradation and PMS activation. nZVI was compared with Fe 2+, Fe 3+ and micro-ZVI and their results indicated high performance of nZVI compared to others. Reusability of nZVI was examined in four cycles. nZVI exhibited that reusability was acceptable in three runs. The results of effect of anions showed that phosphate had significant inhibitory effect on 4-CP degradation in US/PMS/nZVI process. The scavenging experiments indicated that hydroxyl radical had more contribution compared to sulfate radical. Intermediates of 4-CP degradation were identified including five aromatic compounds. Reaction pathway of 4-CP degradation was proposed. Finally, the performance of US/PMS/nZVI process was evaluated on real petrochemical wastewater. The results showed that US/PMS/nZVI can be a suitable pretreatment for biological treatment. Graphical abstract: Image 1 Highlights: nZVI was synthesized and its function was investigated on PMS activation. nZVI/PMS/US was effective to degrade 4-CP. Simultaneous application of nZVI and US boosted PMS activation and 4-CP degradation. Intermediates of 4-CP degradation were also determined. The performance of nZVI/PMS/US was evaluated on petrochemical wastewater treatment.